UHT Cow’s Milk Supplementation Affects Cell Niches and Functions of the Gut–Brain Axis in BALB/c Mice - Felipe S. Lemos; Caio A. Prins; Ana M. B. Martinez; Raul Carpi-Santos; Arthur S. Neumann; Nathalia Meireles-da-Costa; Roberto Luisetto; Valeria de Mello-Coelho; Felipe L. Oliveira (Biomedicines)
Background/Objectives: Cow’s milk is a bioactive cocktail with essential nutritional factors that is widely consumed during early childhood development. However, it has been associated with allergic responses and immune cell activation. Here, we investigate whether cow’s milk consumption regulates gut–brain axis functions and affects patterns of behaviors in BALB/c mice, previously described by present low sociability, significant stereotypes, and restricted interest features. The major objectives consist of to investigate cow’s milk supplementation as possible triggers interfering with cellular niches of the gut–brain axis and behavioral patterns. Methods: Male BALB/c at 6 weeks were randomly divided into two groups, one supplemented with cow’s milk processed at ultra-high temperature (UHT) and another group receiving water (controls) three times per day (200 μL per dose) for one week. Results: Milk consumption disturbed histological compartments of the small intestine, including niches of KI67+-proliferating cells and CD138+ Ig-secreting plasma cells. In the liver, milk intake was associated with pro-inflammatory responses, oxidative stress, and atypical glycogen distribution. Milk-supplemented mice showed significant increase in granulocytes (CD11b+SSChigh cells) and CD4+ T cells in the blood. These mice also had neuroinflammatory signals, including an enhanced number of cortical Iba-1+ microglial cells in the brain and significant cerebellar expression of nitric oxide synthase 2 by Purkinje cells. These phenotypes and tissue disorders in milk-supplemented mice were associated with atypical behaviors, including low sociability, high restricted interest, and severe stereotypies. Moreover, synaptic niches were also disturbed after milk consumption, and Shank-3+ and Drebrin+ post-synaptic cells were significantly reduced in the brain of these mice. Conclusions: Together, these data suggest that milk consumption interfered with the gut–brain axis in BALB/c mice and increased atypical behaviors, at least in part, linked to synapse dysfunctions, neuroinflammation, and oxidative stress regulation.